An uncommon cause of acute abdomen - epiploic appendagitis: CT findings - Nihal USLU TUTAR,; Esra ÖZGÜL,; Dilek OĞUZ,; Banu ÇAKIR,; N. Çağla TARHAN,; Mehmet COŞKUN, (Turkish Journal of Gastroenterology, 2019)
-